Surface Modification of Polyethersulfone (PES) with Ozone. (3rd September 2019) - Lutondo, Shin; Toro, Marc; Sachdev, Shreen; Shertok, Joel; Bailey, Alla; Mehan, Michael; Gupta, Surendra K.; Takacs, Gerald A.
ABSTRACT: Polyethersulfone (PES) is a thermoplastic polymer able to maintain its toughness and stability at high temperatures with applications, such as, in water ultrafiltration. This research focused on altering the surface properties of PES film, making it more water-liking, hydrophilic, and repulsive to organic waste. The oxidative technique used ozone to modify the surface of PES as a function of treatment time. Atomic force microscopy (AFM) measurements did not show significant changes in surface roughness compared to untreated PES. X-ray photoelectron spectroscopy (XPS) detected an increase in concentration of O atoms up to ca. 25 atomic % (at %) and the formation of primarily C–O and sulfonate/sulfate groups due to the reaction of ozone with the C–S bond in PES. The water contact angle (CA) decreased by ca. 28% indicating an increase in hydrophilicity as a result of the formation of polar oxygen moieties on the surface.